The ‘Higgs’ amplitude mode at the two-dimensional superfluid/Mott insulator transition - Endres, Manuel; Fukuhara, Takeshi; Pekker, David; Cheneau, Marc; Schauβ, Peter; Gross, Christian; Demler, Eugene; Kuhr, Stefan; Bloch, Immanuel (Nature (London), 2012)
A ‘Higgs’ mode, signifying the breaking of a continuous symmetry in a model with emergent Lorentz invariance, is found close to the transition to the Mott insulating phase in a two-dimensional neutral superfluid. Higgs excitation in a different guise In relativistic quantum field theory, a broken continuous symmetry leads to the emergence of two types of fundamental excitation: massless Nambu–Goldstone modes and a massive 'Higgs' amplitude mode. An excitation of the Higgs type (made famous through the recent discovery of a Higgs-like boson in particle physics) is expected to appear as a fundamental collective mode in quantum many-body systems. Immanuel Bloch and colleagues unambiguously identify and study a Higgs mode in a two-dimensional neutral superfluid, a first step in the exploration of emergent relativistic models with ultracold atomic gases. Spontaneous symmetry breaking plays a key role in our understanding of nature. In relativistic quantum field theory, a broken continuous symmetry leads to the emergence of two types of fundamental excitation: massless Nambu–Goldstone modes and a massive ‘Higgs’ amplitude mode. An excitation of Higgs type is of crucial importance in the standard model of elementary particle physics 1 , and also appears as a fundamental collective mode in quantum many-body systems 2 . Whether such a mode exists in low-dimensional systems as a resonance-like feature, or whether it becomes overdamped through coupling to Nambu–Goldstone modes, has been a subject of debate 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 . Here we experimentally find and study a Higgs mode in a two-dimensional neutral superfluid close to a quantum phase transition to a Mott insulating phase. We unambiguously identify the mode by observing the expected reduction in frequency of the onset of spectral response when approaching the transition point. In this regime, our system is described by an effective relativistic field theory with a two-component quantum field 2 , 7 , which constitutes a minimal model for spontaneous breaking of a continuous symmetry. Additionally, all microscopic parameters of our system are known from first principles and the resolution of our measurement allows us to detect excited states of the many-body system at the level of individual quasiparticles. This allows for an in-depth study of Higgs excitations that also addresses the consequences of the reduced dimensionality and confinement of the system. Our work constitutes a step towards exploring emergent relativistic models with ultracold atomic gases.